Education and Implementation of Household Composting System to Reduce Waste Generation in Kedungsuren Village, Kaliwungu Selatan, Kendal. - Aden Paiq Muntaz; Muhammad Ilham Prasetya; Irgi M. Aqil Daeng Masiga; Eko Setyo Nugroho; Muhammad Zacky Sulthoni; Nabila Mey Nur Hardini; Fatimah Nisa Royyani; Dwi Ayu Novita; Nur Hijratun Nafiah; Itsna Cholifatun Nisa; Nadya Sya’ada; Anisa Badriyah; Avika Fitriana Assari; Shovi Zaidatul Ma’rifah; Aulia Najwa Zaen; Najichah M.H (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
The program "Education and Implementation of Household Composting System to Reduce Waste Generation in Kedungsuren Village" aims to increase community knowledge and skills in managing organic waste through composting. This activity was held on August 4, 2024, attended by 25 participants from PKK cadres. Through interactive counseling, compost demonstration, and distribution of educational brochures, participants showed a significant increase in understanding of the importance of organic waste management and the composting process. The program results showed that 85% of the participants felt more confident to implement composting practices in their homes, with 17 out of 25 participants understanding the correct way to make compost. Despite the success of this program, challenges such as limited composting tools and the need for more intensive mentoring still need to be addressed. Therefore, suggestions for increased availability of composting tools, continuous mentoring, further training, policy support, and program replication in other areas are needed to ensure the sustainability and long-term success of this program in reducing waste generation in Kedungsuren Village.